Local head loss caused in connections used in micro-irrigation systems - Wagner W. Á. Bombardelli; Antonio P. de Camargo; José A. Frizzone; Rogério Lavanholi; Hermes S. da Rocha (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Information about local head loss caused by connections employed in micro-irrigation systems is hard to be found in literature. The objective of this research was to experimentally determine the local head losses in connections commonly used in micro-irrigation and propose mathematical models using the theorem of Buckingham. The methodology of tests was based on international standards. The tests were carried out under controlled inlet pressure, at 150 kPa, and five to ten units of each connection model were tested. The curves relating flow and head losses were drawn based on 15 flow conditions, obtained under increase and decrease of flow rate. For each condition, 30 points were collected resulting in a sample size of 900 points in each test. For each connection model evaluated, the following information was obtained: curves of local head loss as a function of flow rate and of local head loss coefficient (KL). The obtained values of KL ranged from 2.72 to 24.16, which become constant for Reynolds number higher than 10,000. The sensitivity of the coefficient related to a ratio of the internal sections in the connections was also verified. The flow exponents presented values close to the one applied by the Darcy-Weisbach equation (m = 2). The models developed for the connections presented a satisfactory performance.